Electron gun and collector for RAON EBIS charge breeder. (1st September 2021) - Son, H.J.; Park, Y.H.; Shin, T.; Kondrashev, S.; Chung, M.
Abstract: A heavy-ion accelerator facility, called RAON, is being constructed in Korea. RAON is a large scale experimental facility for basic science research through nuclear physics experiments using various rare-isotope (RI) beams. An Electron Beam Ion Source (EBIS) will be utilized as a charge breeder in the isotope separation on-line (ISOL) system of RAON. The electron gun (e-gun) and electron collector are essential components of the EBIS to charge-breed the RI beams. The e-gun, a magnetically immersed type, has been designed to generate electron beams with currents up to 3 A. The material of the cathode is IrCe, which provide a higher current density and longer lifetime than the LaB6 cathodes. In addition, the collector which can dissipate electron beam power up to 20 kW has been designed and built. A test bench has been designed and constructed to commission the e-gun and collector sub-systems. The test bench is equipped with a negative high-voltage platform, called a cathode platform, to provide an independent electron beam current loop. The control system was also designed and implemented to be able to control two different platforms, such as the cathode and ground platforms, using the NI LabVIEW hardware and software. The experimental goals of the tests described in this paper are to generate and transport to collector 2 A electron beam, and to demonstrate a stable operation mode with electron beam width of 50 ms and a repetition rate of 10 Hz. These goals have been determined for the first charge breeding experiment, which is to obtain the charge-bred beam of Cs 33+, in the future. This paper presents the electron gun and collector sub-system of RAON EBIS, including the cathode tests, the simulation results, and the electron beam experiment.